1000 000 - 728 - 864 464 : 97 + 234 589 =
1000 000 - 728 - 864 464 : 97 + 234 589 == 1 224 949
1000 000 - 728 - 864 464 : 97 + 234 589 == 1 224 9491)864 464 : 97 = 8912
1000 000 - 728 - 864 464 : 97 + 234 589 == 1 224 9491)864 464 : 97 = 89122)1 000 000 - 728 = 999 272
1000 000 - 728 - 864 464 : 97 + 234 589 == 1 224 9491)864 464 : 97 = 89122)1 000 000 - 728 = 999 2723)999 272 - 8912 = 990 360
1000 000 - 728 - 864 464 : 97 + 234 589 == 1 224 9491)864 464 : 97 = 89122)1 000 000 - 728 = 999 2723)999 272 - 8912 = 990 3604)234 589 + 990 360=1 224 949
1 000 000 - 948 - (592 263 : 79 + 178 249) =
1 000 000 - 948 - (592 263 : 79 + 178 249) == 813 306
1 000 000 - 948 - (592 263 : 79 + 178 249) == 813 3061)592 263 : 79 = 7497
1 000 000 - 948 - (592 263 : 79 + 178 249) == 813 3061)592 263 : 79 = 74972)178 249 + 7497 = 185 746
1 000 000 - 948 - (592 263 : 79 + 178 249) == 813 3061)592 263 : 79 = 74972)178 249 + 7497 = 185 7463)1 000 000 - 948 = 999 052
1 000 000 - 948 - (592 263 : 79 + 178 249) == 813 3061)592 263 : 79 = 74972)178 249 + 7497 = 185 7463)1 000 000 - 948 = 999 0524)999 052 - 185 746 = 813 306
1) 15 - x - 2x^2 > 0
2x^2 + 2x - 15 < 0
2x^2 + 2x - 15 = 0
D = b^2 - 4ac = 2^2 -4*2*(-15) = 4 + 120 = 124>0
x_1 = (-b + VD)/2a = (-2 + V4*31)/2*2 = (-2 + 2V31)/4 = 2(-1 + V31)/4 =
= (-1 + V31)/2
x_2 = (-b - VD)/2a = (-1 - V31)/2
Решением является (-1 - V31)/2 < x < (1 + V31)/2
ответ. ( (-1 - V31)/2; (-1 + V31)/2 )